Elevated plasma and urinary concentration of green tea catechins associated with improved plasma lipid profile in healthy Japanese women - Takechi, Ryu; Alfonso, Helman; Hiramatsu, N.; Ishisaka, A.; Tanaka, A.; Tan, L.; Lee, Andy (Elsevier, 2016)
This study investigated green tea catechins in plasma and urine and chronic disease biomarkers. We hypothesized that plasma and urinary concentration of green tea catechins are associated with cardiovascular disease and diabetes biomarkers. First void urine and fasting plasma samples were collected from 57 generally healthy females aged 38 to 73 years (mean, 52 ± 8 years) recruited in Himeji, Japan. The concentrations of plasma and urinary green tea catechins were determined by liquid chromatography coupled with mass tandem spectrometer. Low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglyceride, glucose, insulin, glycated hemoglobin, and C-reactive protein in plasma/serum samples were analyzed by a commercial diagnostic laboratory. Statistical associations were assessed using Spearman correlation coefficients. The results showed weak associations between plasma total catechin and triglyceride (r = -0.30) and LDL cholesterol (r = -0.28), whereas plasma (-)-epigallocatechin-3-gallate, (-)-epigallocatechin, (-)-epicatechin-3-gallate, and (-)-epicatechin exhibited weak to moderate associations with triglyceride or LDL cholesterol, but little associations with HDL cholesterol, body fat, and body mass index were evident. Urinary total catechin was weakly associated with triglyceride (r = -0.19) and LDL cholesterol (r = -0.15), whereas urinary (-)-epigallocatechin-3-gallate (r = -0.33), (-)-epigallocatechin (r = -0.23), and (-)-epicatechin-3-gallate (r = -0.33) had weak to moderate correlations with triglyceride and similarly with body fat and body mass index. Both plasma (r = -0.24) and urinary (r = -0.24) total catechin, as well as individual catechins, were weakly associated with glycated hemoglobin. Plasma total and individual catechins were weakly to moderately associated with C-reactive protein, but not the case for urinary catechins. In conclusion, we found weak to moderate associations between plasma and urinary green tea catechin concentrations and plasma biomarkers of cardiovascular disease and diabetes.